Corral fishing in the Algodoal-Maiandeua Environmental Protection Area (Maracanã, Brazilian Amazon) (Research, Society and Development, 2022)
Corral fishing is one of the most traditional ways of fishing in the coastal zone of Brazilian northern state of Pará. It is a very productive activity, which point out the cultural characteristics, the traditional knowledge and the social profile of the fishermen who perform it. This paper characterizes Corral fishing in the Algodoal-Maindeua Environmental Protection Area (APA Algodoal-Maiandeua), verifying the geographical positions of the corrals and the situation in which they are (active or inactive), considering the type of corral, the vegetal resources used for its construction, its origins, the assembly, the periodicity of the construction and the harvest. The results were obtained through field trips in order to map and define the area of study; identify corral fishermen and apply semi-structured interviews. Based on field surveys, we show that there are 111 corrals in the area, being in greater numbers in the village of Algodoal. The activity is mainly performed by men aged 52 and 85 years.  The vegetable resources frequently used for the manufacture of the corrals are bacuri (Platonia insignis), caraipé (Licania sp.), jarana (Lecythis lurida) and buiuçú (Ormosia coutinhoi). The fish species most captured are Gó (Macrodon ancylodon), Piramutaba [Catfish] (Brachyplatystoma vaillantii), Dourada (Brachyplatystoma flavicans; Brachyplatystoma rousseauxii) and Uritinga (Arius proops), whereas species considered scarce in the region are the Mero (Epinephelus itajara), Tainha (Mugil spp.) and Xaréu (Caranx spp.). The research results provide support for the improvement of the management plan of the APA Algodoal-Maiandeua, as instrument capable of promoting the community and sustainable management of fisheries resources in the protected area.